Gel electrophoresis of proteins : a practical approach - Hames, B. D. (OUP, 1998)
This new edition of Gel Electrophoresis of Proteins is a completely new text, with eight of the ten chapters written by new authors. It presents the best methods, hints and tips for core procedures such as one- dimensional polyacrylamide gel electrophoresis, isoelectric focusing, two-dimensional gel electrophoresis, preparative gel electrophoresis, and peptide mapping, complete with the latest refinements and updates of the procedures. In addition, it describes major new techniques which have come to the fore since the previous edition. Thus there are chapters on capillary gel electrophoresis, sequence analysis of gel-resolved proteins, fluorophore-labelled saccharide electrophoresis, and analysis of protein:protein interactions by gel electrophoresis. One thing has not changed. The emphasis is still on describing the best methods, in step-by-step detail, with copious advice to ensure that each method works first time in the reader's hands. The first two editions of Gel Electrophoresis of Proteins: A Practical Approach each gained a strong reputation as easy-to-follow laboratory manuals written by experienced researchers for researchers. The methods were presented in a clear accessible format and had been fully tested to ensure success in the lab. This new edition will strengthen the reputation of the book still further. It is a 'must have' for all those who currently use gel electrophoresis or who plan to do so.